An Investigation of the Psychosocial Outcomes of Dry Eye Disease Treatment in Children with Computer Vision Syndrome. - Temeltürk, Rahime Duygu; Koçer, Ali Mert; Özal, Ece (Turkish Journal of Ophthalmology / Türk Oftalmoloji Dergisi, 2024)
Objectives: Computer vision syndrome (CVS) is a common disorder among children and is often associated with dry eye disease (DED). While researchers have shown a higher prevalence of psychopathology in older patients with DED, the impact of CVS-induced DED on the psychological state of children is not well known. This study aimed to evaluate psychological outcomes before and after DED treatment in pediatric patients with CVS-related DED. Materials and Methods: In this study, a total of 38 children (32 girls, 6 boys) with CVS-related DED were evaluated with the Schirmer test, tear break-up time (TBUT), ocular surface disease index (OSDI), and Oxford grading scale at the time of diagnosis and after treatment with artificial tear drops. Additionally, quality of life (QoL) and anxiety and depression symptoms were assessed using self-report scales for children. Results: The mean age and mean daily screen exposure of the patients were 13.95±2.42 years and 5.65±2.31 hours, respectively. After treatment, TBUT and Schirmer test values of the patients increased significantly, while OSDI values decreased (p<0.001 for all). The anxiety and depression scores of the patients decreased, while QoL functionality scores increased (p<0.05 for all) following treatment. There were significant correlations between Schirmer test values and anxiety scores (r=-0.32, p=0.045) and QoL total scores (r=0.38, p=0.016). Conclusion: Enhanced QoL and decreased anxiety and depression scores were associated with improved Schirmer test results, indicating that appropriate DED treatment may mitigate the psychosocial effects of CVS-related DED in pediatric patients.